Effect of Addition of Lemongrass Extract (Cymbopogon citratus) On Edible Film From Garut Starch (Marantha arundinaceae L.) As an Antimicrobial - Muthi'ah Muthi'ah; Catur Budi Handayani; Retno Widyastuti; Afriyanti Afriyanti (Universitas Veteran Bangun Nusantara, 2021)
ABSTRACT Edible film is an alternative packaging that does not cause environmental problems, because it is biodegradable. Lemongrass extract (Cymbopogon citratus) contains citronellal, geraniol and citronellol which can inhibit bacterial activity. This study aims to determine the visual appearance, antimicrobial activity, moisture content and thickness of arrowroot starch edible film with various treatments of lemongrass extract levels. This research method used Completely Randomized Design (CRD) with EO0% treatment; EA15%; EB20%; EC25%; ED30%. And it was repeated three times so that 15 treatment units were obtained. The data obtained were calculated using the Analysis of Variance (ANOVA) and if there was a difference, continued with the Duncan's Multiple Range Test (DMRT) test using SPSS 16. The results showed that visually the color of arrowroot starch edible film got darker as the addition of lemongrass extract increased. . The results of statistical calculations show that there is no difference in water content, there is a significant difference in thickness and inhibition of antimicrobial activity using E. coli bacteria. The higher the lemongrass extract, the wider the clear zone formed. The widest clear zone formed was with the addition of 30% lemongrass extract, which was 31 mm, while the control did not form a clear zone.Keywords: Antimicrobial, Arrowroot starch, Edible film, Lemongrass